THE GENERAL ASSOCIATIONS OF ENTREPRENEUR ASSOCIATION OF ECONOMY: YES OR NO - S. Perišić, Vladan (Law - Theory and Practice, 2010)
The general associations of entrepreneur as a place for gathering the bearers of small capital and the basic form of dealing in economic activity are often treated as a marginal part of economic gathering, even though by many indicators of social contribution it deserves better treatment and more dedicated regard of state for the general associations of entrepreneur. The part of such relation of state and society toward them lies in the fact that all of the important shapes of economic activity are founded in the form of economic associations and not in form of entrepreneurs and that theirs evidently bigger economical strength is shown in associations which represent them and they by nature of legal regulations are not members of general associations. At the same time this is area of organizing citizens and legitimate eforts of civil society to improve the state and social community of Serbia. In the Republic of Serbia general associations of entrepreneur are registered on base of Law of Economic Chambers and they represent the basic form of merging of entrepreneurs. Legal frame that allows work of associations is not sufficient for its real and full, economic and social engagement. It is necessary to make a great effort in puning a road toward state partnership in right volume and sense.